Regulation of circadian rhythm and sleep by miR-375-timeless interaction in Drosophila. - Xia, X.; Fu, X.; Du, J.; Wu, B.; Zhao, X.; Zhu, J.; Zhao, Z. (FASEB Journal (Federation of American Societies for Experimental Biology), 2020)
MicroRNAs are important coordinators of circadian regulation that mediate the fine-tuning of gene expression. Although many studies have shown the effects of individual miRNAs on the circadian clock, the global functional miRNA-mRNA interaction network involved in the circadian system remains poorly understood. Here, we used CLEAR (Covalent Ligation of Endogenous Argonaute-bound RNAs)-CLIP (Cross-Linking and Immuno-Precipitation) to explore the regulatory functions of miRNAs in the circadian system by comparing the miRNA-mRNA interactions between Drosophila wild-type strain W1118 and a mutant of the key circadian transcriptional regulator Clock (Clkjrk). This experimental approach unambiguously identified tens of thousands of miRNA-mRNA interactions in both the head and body. The miRNA-mRNA interactome showed dramatic changes in the Clkjrk flies. Particularly, among ~300 miRNA-mRNA circadian relevant interactions, multiple interactions involving core clock genes pdp1, tim, and vri displayed distinct changes as a result of the Clk mutation. Based on the CLEAR-CLIP analysis, we found a novel regulation of the circadian rhythm and sleep by the miR-375-timeless interaction. The results indicated that Clk disruption abolished normal rhythmic expression of miR-375 and the functional regulation occurred in the l-LNv neurons, where miR-375 modulated the circadian rhythm and sleep via targeting timeless. This work provides the first global view of miRNA regulation in the circadian rhythm.